The effects of judicial efficiency on credit market development - Hoang Lan Ha (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2003)
Judicial enforcement of contracts can have an effect on credit market performance because it influences the risk and costs of credit transactions. This paper documents this point by empirically investigating the relation between the efficiency of judicial systems and credit market development around the world. Data from a new database, the World Bank's Doing Business Database, are applied for the research. The efficiency of the judicial system is measured by its speed and simplicity. Regression results show that, apart from traditional variables such as the level of income or inflation rate, indicators of judicial enforcement were also statistically significant in explaining credit market development. Long litigation processes and complex procedures inversely correlated to indicators of credit market development. Countries with better judicial enforcement display more developed credit markets, represented by a larger size of the banking sector and a higher proportion of credit granted to the private sector.
Keywords: 330; Kreditmarkt; Entwicklung; Kredit; Vertrag; Schätzung; Welt; Rechtsdurchsetzung